A Comparison of Four Different Methods of Prediction of Mesiodistal Widths of Unerupted Permanent Canines and Premolars - Jeelani, Waqar; Asad, Washma; Ahmed, Maheen (UI Scholars Hub, 2022)
The success of orthodontic treatment depends upon the accurate assessment of mesiodistal widths of unerupted canines and premolars in mixed dentition stage. There are several methods available for mixed dentition analysis with dubious reliability in our population. Objective: To statistically develop new prediction equations for Pakistani subjects to predict the widths of unerupted upper canines and premolars (U345) and lower canine and premolars (L345) using mesiodistal widths of lower incisors (I1I2) and lower incisors and first molars (I1I2M1) and compare their performance with previously established methods of Moyers and Tanaka-Johnston. Methods: Study was conducted using the data from the dental casts of 200 Pakistani subjects with permanent teeth. Linear regression analysis was used to develop general and gender specific equations for estimation of U345 and L345 using the combined mesiodistal width I1I2 and I1I2M1. The actual and estimated sum of of U345 and L345 as determined by Moyers and Tanaka-Johnston and those from prediction equations based on I1I2 and I1I2M1 were compared using the paired sample t-test. Results: There were signficant differences in the actual mesiodistal widths of U345 and L345 and those calculated using Tanaka-Johnston and Moyers methods. Newly developed equations based on I1I2 and I1I2M1 performed better than the Moyers and Tanaka-Johnston methods in both the arches. Conclusion: Moyers and Tanaka-Johnston analyses generally overestimated U345 and L345 dimensions. The newly developed prediction equations based on I1I2 and I1I2M1 performed better for the prediction of mesiodistal widths of U345 and L345.